2013
DOI: 10.1016/j.repce.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial adjustment, psychiatric morbidity and quality of life in adolescents and young adults with congenital heart disease

Abstract: ResumoObjetivos: Caracterizar a população de adolescentes e jovens adultos com cardiopatias congénitas (CC) ao nível do seu ajustamento psicossocial e morbilidade psiquiátrica, bem como avaliar a qualidade de vida (QV), para perceber quais são as variáveis com impacto na vida e na adaptação à doença. População e métodos: Participaram 74 pacientes com CC, sendo 41 do sexo masculino e 33 do sexo feminino, com idades entre 12-26 (média = 18,76 ± 3,86). Foram recolhidos os dados demográficos e clínicos mais releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 27 publications
(37 reference statements)
0
7
1
Order By: Relevance
“…Coelho et al 37 reported that better social supports contributed to improvement of physical quality of life; however, in our study, none of the types of social supports significantly predicted the Physical Super-Dimension of HRQoL.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Coelho et al 37 reported that better social supports contributed to improvement of physical quality of life; however, in our study, none of the types of social supports significantly predicted the Physical Super-Dimension of HRQoL.…”
Section: Discussioncontrasting
confidence: 95%
“…These patients had worse psychosocial adjustment as they required constant care from their caregivers and had limited exposure to school and leisure activities. Patients with complex CHD were also found to have more negative thoughts and internalisation 37 …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In clinical classification systems such as the DSM-IV, internalizing problems are described as emotional problems that can include disorders such as anxiety and depression, while externalizing or behavior problems comprise disorders such as ADHD or antisocial behavior [ 18 ]. In addition, children with CHD are reported to have a higher lifetime prevalence of psychiatric disorders, such as attention deficit/hyperactivity disorder (ADHD) or anxiety disorders [ 19 , 20 , 21 ]. Still, a recent review found most of these dysfunctions to be high in prevalence but mild [ 8 ], which accounts specifically for less severe conditions, as with VSD [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, results on the perceived HRQOL of children with CHD are still inconsistent. Some studies reported satisfactory overall HRQOL with no differences or even better scores compared to non-affected controls [ 19 , 27 , 28 , 29 ], whereas other studies found these children to be at a greater risk of impaired HRQOL [ 30 , 31 , 32 ]. These differences could be attributed to variability in method designs, such as the age of the children at the time of assessment [ 33 ] or the severity of CHD [ 32 ].…”
Section: Introductionmentioning
confidence: 99%